Effect of high intensity interval training on elite athletes' antioxidant status - Nongkhai, K. (Journal of Athletic Enhancement, 2021)
High-Intensity Interval Training( HIIT) is a form of interval training, a cardiovascular exercise strategy interspersing short ages of violent anaerobic exercise with lower violent recovery ages, until too exhausted to continue. The system isn't just confined to cardio and constantly includes weights for the short ages as well. Though there's no universal HIIT session duration, these violent exercises generally last fewer than 30 twinkles as it uses the anaerobic energy systems which are generally used for short, sharp bursts. The times vary, grounded on a party's current fitness position. Likewise, traditional HIIT was designed to be no longer than 20 seconds on with no further than 10 seconds out. This would bring in the anaerobic energy system. The intensity of HIIT also depends on the duration of the session. HIIT exercises give bettered athletic capacity and condition as well as bettered glucose metabolism. Compared with longer sessions typical of other rules, HIIT may not be as effective for treating hyperlipidemia and rotundity, or perfecting muscle and bone mass. Still, exploration has shown that HIIT rules produced significant reductions in the fat mass of the whole- body in youthful women. Some experimenters also note that HIIT requires "an extremely high position of subject provocation "and question whether the general population could safely or virtually tolerate the extreme nature of the exercise authority.